Estimación de un perfil regional de presión de poro para un segmento del sector central del Valle Medio del Magdalena a partir de información geológica y geofísica, para la identificación de presiones anormales (2020)
Hydrostatic control in the design of a well is one of the most important safety factors in the drilling operation since it has historically been the cause of major disasters within the oil industry; this hydrostatic control is given by the formation pressure and fracture pressure, which constitute a fundamental basis for the programming of drilling mud and adequate depths for the settlement of the casing. These pressures are determined by using direct or indirect estimation methods. The study segment of this work, located in the central sector of the VMM basin, has a high YNC prospectivity thanks to its large extensions and thicknesses of low permeability Cretaceous source rock. This segment does not have a regional pore pressure profile that shows the lateral variations of this property, to reduce the operational risks caused by abnormal pressure conditions, since, historically, fields adjacent to this segment have suffered problems of this type due to the lithological, tectonic, stratigraphic and geochemical configuration of this part of the basin.